Preparing a cost control plan for a contracting company VR:00 (05-2019) - Senjab, Mohamad Muhanad Ahmad (Journal of engineering sciences and information technology, 2024)
Objectives: Spreading knowledge about how to control project costs during its implementation. Methods: Starting with an introduction to the concept of the cost control plan and its difference from accounting books that do not give results about the project status until after completion. The research shows the relationship between the cost control plan assigned to the project implementation phase and the value engineering that it includes in addition to the design and operation phase. It deals with explaining the cost control cycle (cost estimation - budget - monitoring - analysis - correction - re-estimation) and supporting it in a developed explanatory manner that shows the relationships between the parties participating in it (site, warehouses, contracts, accounts, equipment and machinery, project management, financial management, senior management). Then it explains the application mechanism by identifying cost centers and the cost baseline, then monitoring costs of all types (materials, equipment, labor, contractors, services, miscellaneous expenses, etc.) And controlling them according to models attached at the end of the research, then comparing, analyzing and updating using technical tools, especially the earned value and the cost performance factor. A table was attached that shows the project status according to the technical indicators, as well as a typical cash flow chart showing the technical value discrepancies taken from one of the references. Results: Available expertise and business models were collected and authenticated from references, and an Excel program was created to calculate the discrepancies between the acquired and targeted values, calculate the technical performance factors to predict the project status upon completion, and calculate the remaining cost estimate in order to make recommendations. Conclusions: Obtaining a document of procedures and models for a simplified project implementation cost control plan suitable for contracting companies.